Impact of social factors on health practices of the elderly: an analytical study in rural Surendranagar - Nagar, Shashwat; Nagar, Noopur; Nagar, S. S.; Mahyawanshi, Darshan; Kartha, Girija P. (International Journal of Research in Medical Sciences, 2017)
Introduction: Increased attention to health promotion and disease prevention are important for the appropriate care of the elderly. With the increasing life expectancy, a focus on preventive measures to decrease morbidity and improve quality of life in old age has also developed. To that end, health behavior and lifestyle have become important areas of concern over the last 20 years. Social factors lay a significant impact on the health practices. This study was therefore taken up to study the above factor and draw conclusions. Aims and objectives: 1. To study the various health practices of the elderly. 2. To find out association between the socio demographic features and the prevailing health practices. Methods: A Cross sectional analytical study was carried out. All the subjects were interviewed personally to know the details and were treated with due respect after a consent. Out of all the talukas in rural Surendranagar, Sayla was selected randomly after which Sayla village was selected in a similar manner from all the villages in the talukas. Results: The mean age of the subjects was 68±7.5. Majority of the subjects were unemployed and illiterate (58%). Social factors like Social class, staying with children and staying in joint family were significantly associated with good health practices. Conclusions: The Health practices of the elderly can be improved upon by large scale health education programmes which can be targeted on the age group. Patient compliance improvement can be achieved by explaining them about the disease and treatment protocol in detail at the time of their health visit.